Alcoholic Liver Disease. Issue 2 (10th March 2022) - Higuera‐de‐la‐Tijera, Fátima; Lira‐Vera, Jorge Emilio; Morales‐Gutiérrez, Oscar; Martínez‐Castillo, Moisés; Medina‐Ávila, Zaira; Servín‐Caamaño, Alfredo; Pérez‐Hernández, José Luis; Gutiérrez‐Reyes, Gabriela
Abstract :